STUDI TENTANG KINERJA TENAGA PENJUALAN (Study of Performance of Sales Persons) - Retno Mulatsih (STIE Pelita Nusantara Semarang, 2011)
This study will analyze factors that have influence on increase of performance of sales persons, through quality of sales territory design, effectivity of sales persons’s activity, level of experience in selling, technical competence of sales persons and its relevance to the increase of performance of sales persons. This study model uses five hypotheses, that is the better the quality of sales territory design the more effective the activity of sales persons, the higher the level of experience of sales persons in selling the higger the technical competence of sales persons, the higher the technical competence of sales persons the more effective the activity of sales persons, the higher the technical competence of sales persons the higher the performance of sales persons. The technique of sample collection that was used in this study was purposive sampling method, where sample was selected with terms/conditions that were consideres as having essential characterictics that were relevant to this study. The respondents used here were 100 respondents that is the sales persons of PT. Sinar Niaga Sejahtera Distribution Area of Central Java I that have worked for the company for more than one year. The data analysis technique that was used here was the structural equation modeling ( SEM ) from AMOS 16.0 software package in modeling and review of hypotheses. The results of data analysis will explain the causality relation amongst variables that are being developed in this study model.